Tanggung Jawab sebagai Nilai dari Praktik Akuntansi Zakat: Studi Etnometodologi Islam - Thalib, Mohamad Anwar (Institut Agama Islam Negeri (IAIN) Madura, 2023)
This study aims to reveal the local cultural values of zakat fitra accounting practices. This research uses the Islamic paradigm. The approach used is Islamic ethnomethodology. There are five data analysis stages: charity, knowledge, faith, revelation information, and courtesy. The results of the study indicate that there is a value of responsibility behind the accounting practice of distributing zakat fitra. This value is reflected through the actions of the amil zakat, who use data from the government, data and advice from residents about citizens who are entitled to receive zakat fitra, amil zakat coordinators who distribute zakat not only to less fortunate citizens but amil officers who are by the Shari'a Islam. As well as the decision of the amil to distribute zakat funds three days before Eid al-Fitr. It is intended that zakat recipients can use these funds to meet their needs. In the Islamic culture of Gorontalo, the value of responsibility is often advised through the expression (lumadu)